Maternal Distress/Coping and Children's Adaptive Behaviors During the COVID-19 Lockdown: Mediation Through Children's Emotional Experience - Petrocchi, Serena; Levante, Annalisa; Bianco, Federica; Castelli, Ilaria; Lecciso, Flavia (Frontiers in Public Health, 2020)
The present study focused on the psychological impact that the lockdown due to coronavirus disease-19 (COVID-19) had on families in Italy. During the COVID-19 pandemic, the Italian government imposed a strict lockdown for all citizens. People were forced to stay at home, and the length of the lockdown was uncertain. Previous studies analyzed the impact of social distance measures on individuals' mental health, whereas few studies have examined the interplay between the adults' functioning, as parents, during this period and the association with the child's adjustment. The present study tested if maternal distress/coping predicts children's behaviors during the COVID-19 lockdown, hypothesizing a mediation effect via children's emotional experience. Participants were 144 mothers (Mage = 39.3, 25–52, SD = 5.6) with children aged 5–10 years (Mage = 7.54, SD = 1.6, 82 boys); mothers answered to an online survey. Results indicated that mothers with higher exposure to COVID-19 showed higher levels of distress and higher display of coping attitudes, even if in the structural equation modeling model, the COVID-19 exposure was not a predictor of mothers' distress. Compared with mothers with good coping skills, mothers with higher stress levels were more likely to attribute negative emotions to their children at the expense of their positive emotions. Moreover, children's emotions acted as mediators between maternal distress/coping and children's adaptive/maladaptive behaviors. In conclusion, it is important to support parents during pandemic emergence, by providing them with adequate information to manage the relationship with their children, to reduce their level of distress and to enhance their coping abilities.